Check whether the following are quadratic equations:
$(x – 3) (2x + 1) = x (x + 5)$


Given:

Given equation is $(x – 3) (2x + 1) = x (x + 5)$

To do:

We have to check whether the given equation is quadratic.

Solution:

The standard form of a quadratic equation is $ax^2+bx+c=0$.

$(x – 3) (2x + 1) = x (x + 5)$

$x(2x+1)-3(2x+1)=x(x)+x(5)$

$2x^2+x-6x-3=x^2+5x$

$2x^2-x^2-5x-5x-3=0$

$x^2-10x-3=0$ is of the form $ax^2+bx+c=0$

Therefore, $(x – 3) (2x + 1) = x (x + 5)$ is a quadratic equation. 

Tutorialspoint
Tutorialspoint

Tutorialspoint Tag Line